A new approach to analyzing groundwater trough its manifestations in the landscapes and toponymy: "Subtle" Hydrogeology - Villarroya, Fermín; Pérez-Cueva, Alejandro J.; Fansa, Ghaleb (Geographicalia, 2019)
“Subtle Hydrogeology” refers to the set of groundwater manifestations and processes in minuscule aquifers in a particular land area that, in many cases, involve human and social dimensions. These are apparently insignificant features, but they conceal the ancient secrets of groundwater and the landscape. Groundwater associated with multilayer low-permeability formations with little saturated thickness hardly has any commercial value. It is, however, a valuable resource for traditionally rural societies, and has given rise to a wide range of ecological, cultural, heritage-related, and toponymic manifestations. These manifestations are studied here in the upper Alfambra basin (Teruel, Spain), from both a geological and a hydrogeological perspective, and from the viewpoint of culture and heritage (with springs, seepages and specific toponymy). For this novel view which contemplates and studies the relationship of groundwater and the landscape, expressed through a specific toponymy (hydronymy), the term “subtle hydrogeology” will be used.